Induction of lncRNA NORAD accounts for hypoxia-induced chemoresistance and vasculogenic mimicry in colorectal cancer by sponging the miR-495-3p/ hypoxia-inducible factor-1α (HIF-1α). Issue 1 (1st January 2022) - Zhang, Lei; Wu, Huili; Zhang, Yong; Xiao, Xingguo; Chu, Feifei; Zhang, Li
ABSTRACT: Hypoxic microenvironment represents the hallmark of solid tumors including colorectal cancer (CRC) and facilitates angiogenesis and chemoresistance, leading to poor prognosis. lncRNA NORAD acts as an oncogenic gene to orchestrate cancer progression by regulating cell proliferation and migration. Notably, an emerging study corroborates the elevation of NORAD during hypoxic conditions in pancreatic cancer. Nevertheless, its biological role in hypoxia-evoked CRC remains unclear. Herein, enhanced expression of NORAD and hypoxia-inducible factor-1α (HIF-1α) was validated in CRC tissues. Furthermore, there was a positive association between NORAD and HIF-1α in CRC tissues. CRC cells exposed to hypoxia exhibited a stronger ability to form vasculogenic mimicry (VM) and resistance to 5-fluorouracil (5-FU), concomitant with higher expression of NORAD. NORAD knockdown restrained hypoxia-induced VM formation and VM marker VE-cadherin expression. Moreover, knockdown of NORAD counteracted CRC cell resistance to 5-FU by decreasing cell viability and increasing cell apoptosis. Additionally, NORAD loss reduced hypoxia-induced HIF-1α expression and subsequent epithelial-mesenchymal transition (EMT) by increasing E-cadherin and inhibiting N-cadherin expression. Intriguingly, HIF-1α overexpression reversed NORAD downregulation-mediated inhibition of VM formation and 5-FU resistance. There was a low expression of miR-495-3p in CRC tissues. Furthermore, NORAD could act as a competitive endogenous RNA of miR-495-3p to regulate HIF-1α. Importantly, inhibition of miR-495-3p muted the efficacy of NORAD loss in hypoxia-induced EMT, VM, and chemoresistance. Thus, the current data highlight that NORAD knockdown may antagonize hypoxia-triggered CRC malignancy by suppressing VM formation and chemoresistance by sponging miR-495-3p/HIF-1α to regulate EMT, supporting a promising therapeutic target for refractory hypoxia in CRC.